Bioethics curriculum in medical schools in Portuguese-speaking countries - Ana Carolina Alvares Lavigne de Lemos Tavares; Ana Gabriela Alvares Travassos; Francisca Rego; Rui Nunes (BMC Medical Education, 2022)
Abstract Background A curriculum is a fundamental tool for educators, and teaching bioethics is fundamental to good medical practice. Studies report a lack of consensus on the teaching of bioethics in undergraduate medicine, and a critical issue is that there remain no minimum curricular parameters. This study performed an analysis between the bioethics curricula of the medical schools of Brazil and Portugal and UNESCO’s Core Curriculum, in addition to proposing key criteria for designing a core bioethics curriculum. Methods This is a cross-sectional, descriptive study that analyzes the bioethics curricula of the medical schools in Brazil and in Portugal. The design of the study includes a qualitative summative content analysis-based approach and a quantitative analysis by means of descriptive statistics. Results Bioethics is taught in both Brazil and Portugal in a diversified way. The results showed that 65.5% of the medical schools analyzed provided at least the 30-h minimum workload recommended by the UNESCO Core Curriculum. Furthermore, bioethics sporadically offered at the end of the medical program in the vast majority of schools studied. Conclusions The most important points to take away from this study are the diversity of the curricular structure of bioethics courses and the lack of formalization of bioethics in the curricula of medical schools in Brazil and Portugal. Given the value of bioethics in clinical practice, we propose that medical schools in Portugal and Brazil update their curricula to encompass minimum criteria, which should be similar to one another and based on common sources, but which should also be tailored to each culture.